Comparative analysis of trichomonad genome sizes and karyotypes - Zubácová, Zuzana; Cimbůrek, Zdenek; Tachezy, Jan (Molecular and biochemical parasitology, 2008)
In parasitic protists, the genome sizes range from 2.9Mb in Encephalitozoon cuniculi to about 160Mb in Trichomonas vaginalis. The suprisingly large genome size of the former human parasite resulted from the expansion of various repetitive elements, specific gene families, and possibly from large-scale genome duplication. The reason for this phenomenon, as well as whether other trichomonad species have undergone a similar genome expansion, is not known. In this work we studied the genomes of nine selected species of the Trichomonadea group. We found that each species has a characteristic karyotype with a stable and haploid number of chromosomes. Relatively large genome sizes were found in all the tested species, although over a rather broad range (86-177Mb). The largest genomes were typically observed in the Trichomonas and Tritrichomonas genera (133-177Mb), while Tetratrichomonas gallinarum contains the smallest genome (86Mb). The genome size correlated with the cell volume, however, no relationship between genome size and the site of infection or trichomonad phagocytic ability was observed. The data presented here provide primary information towards selecting a trichomonad species for future large-scale sequencing to elucidate the evolution of unusual parabasalid genomes.
Keywords: karyotypizace; fylogeneze; Trichomonadida; haploidie; Cell Size; Genome, Protozoan; Haploidy; Animals; velikost buňky; Phylogeny; zvířata; genom protozoální; Karyotyping